5x-2x-(x-6)=16-(-7x-6)-3(8-x)

Simple and best practice solution for 5x-2x-(x-6)=16-(-7x-6)-3(8-x) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5x-2x-(x-6)=16-(-7x-6)-3(8-x) equation:



5x-2x-(x-6)=16-(-7x-6)-3(8-x)
We move all terms to the left:
5x-2x-(x-6)-(16-(-7x-6)-3(8-x))=0
We add all the numbers together, and all the variables
5x-2x-(x-6)-(16-(-7x-6)-3(-1x+8))=0
We add all the numbers together, and all the variables
3x-(x-6)-(16-(-7x-6)-3(-1x+8))=0
We get rid of parentheses
3x-x-(16-(-7x-6)-3(-1x+8))+6=0
We calculate terms in parentheses: -(16-(-7x-6)-3(-1x+8)), so:
16-(-7x-6)-3(-1x+8)
determiningTheFunctionDomain -(-7x-6)-3(-1x+8)+16
We multiply parentheses
-(-7x-6)+3x-24+16
We get rid of parentheses
7x+3x+6-24+16
We add all the numbers together, and all the variables
10x-2
Back to the equation:
-(10x-2)
We add all the numbers together, and all the variables
2x-(10x-2)+6=0
We get rid of parentheses
2x-10x+2+6=0
We add all the numbers together, and all the variables
-8x+8=0
We move all terms containing x to the left, all other terms to the right
-8x=-8
x=-8/-8
x=1

See similar equations:

| 9m+3-7m=17 | | 3(x+4)=15+x | | b-2=-8+b | | 2x^+6x-95=0 | | |6−2x|=−8x | | 5m+4m+2=-25 | | -5+25x+5-40x-10=4x-8x | | 7x+21x-1=7(4x+7) | | 1.5(15b-7)=3b-9 | | |6−2x|=−8 | | -1+n-7-6n=-8-5n | | 8d-2=6 | | 1/4(3x-8)=7 | | x-3/7=1/x+3 | | 100x*0.12=95 | | 28=18x | | x3+3x2+3x+2=0 | | 4(4x-4)-5(5x-3)=0 | | 0.052x+5.203=0.040x+5.197 | | 5+6n=10+3n | | 3+3m+m=2m+5 | | 245+132=q | | (-4)×(2x+3)=5×(-3x-4) | | 5/6=1x/3 | | 7T=3=8t=7T | | 7y+2y=20 | | y/5+y/2=6/7 | | 4|2z+9|=32 | | 7t=3=8=7t | | 562/100=x/32 | | 13-1(2w-19)=5w-24 | | 2.5n=1.10=1.5(n=4) |

Equations solver categories